Task planning and formal control of robotic assembly systems: A Petri net-based approach - Gökhan Gelen; Yasemin İçmez (Ain Shams Engineering Journal, 2024)
In modern industrial production, robotic assembly systems play a crucial role. As robots take on more tasks, the need for formal methods arises to define, control, and execute these tasks. This paper introduces a comprehensive approach to designing and generating control code for robotic assembly systems, taking task sequence planning into account. This methodology utilizes Petri nets (PNs) as a formal modeling and synthesis tool for the controller. Initially, the task sequences for assembly operations are represented using PN formalism. Supervisors are then synthesized for task sequence control specifications. Finally, the control code is obtained by the proposed methodology for industrial robots. By implementing this supervisory control structure, real-time control of the robotic assembly system is achieved. Experimental studies were conducted using an assembly cell equipped with an industrial robot. This methodology bridges the gap between the design and implementation of formal controllers for industrial robots. The proposed approach integrates formal methods into robot programming to leverage several advantages, including correctness assurance, complexity handling, improved documentation and clarity, enhanced safety and reliability, property verification, and scalability.